Identifikasi Senyawa Kimia Fenolik Dalam Ekstrak Etil Asetat Kulit Buah Jengkol (Archidendron pauciflorum (Benth.) I.C Nielsen) - ahmad sopian pian (Viva Medika, 2019)
Jengkol (Archidendron pauciflorum (Benth.) I.C Nielsen) is a plant that is already familiar inIndonesia and is widely used as a processed food that is quite popular. One of the underutilized parts ofthe jengkol plant is the skin. Jengkol fruit peel contains alkaloid compounds, flavonoids, tannins,glycosides, sapoinin and steroids or triterpenoids. The purpose of this study was to determine the contentof chemical compounds in ethyl acetate extract of jengkol fruit peel, and to test antioxidant activity byDPPH free radical reduction method. The results of isolation, purification in ethyl acetate extract ofjengkol fruit skin does not provide activity as an antioxidant. The results of the analysis using FTIRspectrophotometry, Gas chromatography-Mass Spectrometry (GC-MS) and Nuclear Magnetic ResonanceSpectroscopy ( 1 HNMR).